"Animal Introduction" Application For Children - Fadjaruddin Qadr; Agung Budi Prasetijo; Ike Pertiwi Windasari (Ultimatics : Jurnal Teknik Informatika, 2019)
Introducing animals in early childhood can foster children's love for animals. Some media for introducing animals to children are diverse, one of which is a book about animals. Books about animals display various types of animals and information on these animals. But books about animals are less effective in helping parents teach children about animals because they are less interactive. With the development of technology, especially smart phones can help users spread information. Smartphones can load images, videos& text. To help parents introduce animals to children, an animal recognition application on smart phones was developed. The development method used is MDLC, which consists of 6 stages: concept, design, material collection, merging, testing, and distribution. This application is made using the Java programming language on Android with Android Studio. This applications can be used as an interactive learning media to introduce animals to children. This application can display images, videos, animal information and some quizes.